The symbolic connotations of tattoos and their reflections in contemporary Iraqi painting (The Peerian Journal, 2023)
Tattoo art appears in many works of art by contemporary artists, as tattoo is a form of art and symbols of many concepts and has been used for many purposes with meanings for people. This led us to several questions.